On the International Use of Currencies : The Case of the Deutsche Mark. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper assesses the role of the deutsche mark as a key international currency. It first investigates the theoretical basis underlying the international use of a currency. Theoretical considerations indicate that several factors relating to the issuing country-including inflation performance, openness of financial markets, and trade patterns-combine to propagate the international use of its currency. The paper then discusses these factors as they relate to the deutsche mark and identifies trends in several of these determinants of international currency use that presage an expanding role for the mark. Finally, data are presented on the extent of the internalization of the deutsche mark during the 1980s which corroborate the theoretical findings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet